Erebos : it's a game : it watches you - Poznanski, Ursula, 1968-; Pattinson, Judith (Toronto : Annick Press, 2012)
When sixteen-year-old Nick Dunmore receives a package with a mysterious computer game called Erebos, he hopes it will explain his classmates' strange behavior. He is quickly drawn into the cryptic world of the game, where players must obey a strict code. Erebos watches its players and begins to manipulate their lives in frightening ways. It soon becomes clear the game has a deadly agenda. When Nick sets out on a dangerous mission, reality and the virtual world begin to blur.
Translation of German book with same title.
Keywords: Computer games -- Juvenile fiction; Young adult fiction; Science fiction; Suspense fiction